Late presentation of intraperitoneal rupture of the urinary bladder. Issue 606 (April 1976) - Williams, N. S.
Abstract : A case of silent intraperitoneal rupture of the bladder is presented. The extreme biochemical abnormalities which may occur in this rare condition are well illustrated in this case.